Diagnostic Accuracy of CHROMagar Orientation for Identification of Uropathogens - Ali, Nayab; Hussain, Wajid; Mirza, Irfan; Niazi, Asima; Rubab, Fatima; Salim, Saira (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of CHROMagar Orientation for its ability to support the growth and identification of uropathogens by keeping API 20E/20NE as a gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jun to Nov 2019. Methodology: A total of 470 midstream specimen of urine from patients suspected of UTIs were analyzed. Urine specimens were inoculated by 1µL calibrated sterilized loop each on CLED Agar, Blood agar and CHROMagar Orientation media plates.Culture plates were incubated at 35.00±2.00ºC for 18 to 24 hours. As per standard protocols, isolates were identified by colony morphology, Gram stain, catalase, oxidase, DNAase, coagulase, and API 20E/20NE. In addition, the appearance of microorganism on CHROMagar Orientation media were identified according to the manufacturer’s instructions. Results: Out of 470 samples, 211 showed no growth, 90 were classified as mix growth (polymicrobial), and 169 samples were positive (unimicrobial) for the growth of uropathogens. All the samples positive for bacterial growth on conventional media were also positive on CHROMagar orientation and vice versa. The sensitivity and specificity of CHROMagar Orientation for differentiation of uropathogens were 99% and 100%, respectively. Conclusion: The overall findings of our study suggested that CHROMagar supports the growth of all uropathogens. It provided the rapid identification of organisms based on their colour morphology, even in a mixed bacterial culture, growth within 24 hours easily.